2021
DOI: 10.1177/1534735420977666
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Exercise and Nutritional Intervention on Circulating Biomarkers and Metabolomic Profiling During Adjuvant Treatment for Localized Breast Cancer: Results From the PASAPAS Feasibility Randomized Controlled Trial

Abstract: Purpose: Exercise has been shown to improve physical and psychological conditions during cancer therapy, but mechanisms remain poorly understood. The purpose of the present study was to report the results of cancer-related biomarkers and metabolomics outcomes from the PASAPAS feasibility study. Methods: In the PASAPAS randomized controlled trial, 61 women beginning adjuvant chemotherapy for localized breast cancer were randomized in a 6-month program of weekly aerobic exercises associated with nutritional coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 49 publications
3
22
0
1
Order By: Relevance
“…25,26 In line with our results, one previous study conducted by Febvey-Combeset et al found reductions in insulin, glucose, and leptin after a 6 months aerobic exercise program and nutrition counseling, as well as improvements in body composition in breast cancer patients receiving treatment. 26 In contrast, Basen-Engquist et al conducted a weight management program including diet counseling and resistance training over approximately 6 months during breast cancer chemotherapy with no differences for glucose, insulin, leptin or adiponectin compared with usual care, however the intervention group showed modest weight loss. 25 The enhanced exercise-induced effects on MetS and associated biomarkers in our study may be a result of high adherence, the high number of women with MetS at baseline, supervised in-person exercise program, and the inclusion of HIIT.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…25,26 In line with our results, one previous study conducted by Febvey-Combeset et al found reductions in insulin, glucose, and leptin after a 6 months aerobic exercise program and nutrition counseling, as well as improvements in body composition in breast cancer patients receiving treatment. 26 In contrast, Basen-Engquist et al conducted a weight management program including diet counseling and resistance training over approximately 6 months during breast cancer chemotherapy with no differences for glucose, insulin, leptin or adiponectin compared with usual care, however the intervention group showed modest weight loss. 25 The enhanced exercise-induced effects on MetS and associated biomarkers in our study may be a result of high adherence, the high number of women with MetS at baseline, supervised in-person exercise program, and the inclusion of HIIT.…”
Section: Discussionsupporting
confidence: 91%
“…In this regard, while several studies have explored the effects of exercise on MetS associated biomarkers in breast cancer survivors, 24 only a few studies have targeted women with breast cancer undergoing chemotherapy, and have shown inconsistent results. 25,26 In line with our results, one previous study conducted by Febvey-Combeset et al found reductions in insulin, glucose, and leptin after a 6 months aerobic exercise program and nutrition counseling, as well as improvements in body composition in breast cancer patients receiving treatment. 26 In contrast, Basen-Engquist et al conducted a weight management program including diet counseling and resistance training over approximately 6 months during breast cancer chemotherapy with no differences for glucose, insulin, leptin or adiponectin compared with usual care, however the intervention group showed modest weight loss.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, another study focused on the effect of an anti-inflammatory diet, revealed a positive relationship between IL-6 and BMI in breast cancer patients ( 63 ). In a few of the studies reviewed here-in, there was no difference or IL-6 level change following their respective interventions ( 69 , 70 , 88 ). Other note-worthy findings relative to breast cancer did include those found by Matsumoto et al.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, CA15-3, Type 1 T helper cells (Th1), C-reactive protein (CRP), and VEGF were also used in more than three studies for breast cancer for the purpose of diagnosis and treatment ( 30 , 33 , 51 , 54 , 59 , 61 , 63 , 66 , 78 , 79 ). Other biomarkers like insulin, C-C motif chemokine ligand 2 (CCL2), transforming growth factor β 1(TGF-β1), and Treg-like molecule (Treg: Regulatory T cells) were also discussed in some of our reviewed publications, regarding their relevance primarily to breast cancer treatment ( 75 , 76 , 80 , 83 , 84 , 88 , 90 ).…”
Section: Resultsmentioning
confidence: 99%